Prime evil and its many faces in the Book of Revelation - De Villiers, Pieter G. R. (Neotestamentica, 2000)
This article investigates the descriptionption and names of the dragon in Revelation 20:1-3 and 7-10. The context and composition of Revelation 20 are analysed. The relationship with Revelation 12 is explored and the prominence and function of the names of the dragon pointed out. The names are then investigated on their own, especially in the light of the role of names generally and names of evil characters in the rest of the book. It is, finally, also indicated how the names and descriptionptions of the dragon are closely related toand determined in meaning by the seven letters.